Identity reconstruction among people with physical disabilities practising Race Running - Kossakowski Radosław; Witecka-Wiese Maria; Mańkowski Dobrosław (Sciendo, 2021)
The main aim of the article is to present the results of research concerning the reconstruction of the identity of people with disabilities who practice Race Running. In the scientific literature focused on disability, sport is presented as one of the important elements serving for the reconstruction of the identity of people with disabilities and their integration, inclusion with the surrounding social world. However, previous studies did not analyze in this context the role of Race Running, which is a niche, developing sport discipline. Therefore, this article fills a significant gap in the scientific literature dedicated to the role of sport in the reconstruction of the identity of people with disabilities by undertaking an analysis of sport, which has not been the subject of research so far. Starting from the concept of 'pendulum' developed by Karen K. Yoshida, the following article provides a model of identity reconstruction based on five processes: Socialising, Becoming independent, Exposing, Proving, Realizing. The conceptualization of this model is based on the results of qualitative research using the in-depth interview technique. The respondents were people with disabilities practicing Race Running in Poland, their family members and their coaches. The results of the research show not only the possibilities for people with disabilities, which comes with practicing Race Running, but also limitations, because the specificity and technical requirements of this sport mean that its benefits can only be used by people with a certain type of disability.